Linguistics Features of Three British Female Beauty Youtubers - Rahma Aulia Indra; Rina Marnita; Ayumi Ayumi (Vivid: Journal of Language and Literature, 2018)
This article concerns with the characteristics of the language of three British female Youtubers. It is aimed in particular to find out women's linguistic features in their language based on Lakoff's theory (1975) and the functions of each features according to Holme's theory (2013). The result of the study reveals  seven women's linguistic features  in the youtubers' language. They are (1) lexical hedges or fillers, (2) tag questions, (3) „empty‟ adjectives, (4) precise color terms, (5) intensifiers, (6) „superpolite‟ forms, and (7) emphatic stress. Among these features, the intensifiers. appears as the dominant one. The study also shows that each feature has specific function.